2017
DOI: 10.3390/informatics4030020
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Construct of an Expert Evidence-Adaptive Knowledge Base for a Pressure Injury Clinical Decision Support System

Abstract: Abstract:The selection of appropriate wound products for the treatment of pressure injuries is paramount in promoting wound healing. However, nurses find it difficult to decide on the most optimal wound product(s) due to limited live experiences in managing pressure injuries resulting from successfully implemented pressure injury prevention programs. The challenges of effective decision-making in wound treatments by nurses at the point of care are compounded by the yearly release of wide arrays of newly resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Access to 6 articles was not possible, and 11 were excluded for different reasons (see Multimedia Appendix 2 ). Hence, 16 studies [ 16 - 31 ] met all the eligibility criteria and were included in this review. A flow diagram of the selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Access to 6 articles was not possible, and 11 were excluded for different reasons (see Multimedia Appendix 2 ). Hence, 16 studies [ 16 - 31 ] met all the eligibility criteria and were included in this review. A flow diagram of the selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…General characteristics of included studies are shown in Multimedia Appendix 3 . Included studies were conducted between 1995 to 2017 in the following countries: United States of America [ 16 , 17 , 20 , 21 , 25 - 27 ], Italy [ 18 ], Canada [ 19 ], Norway [ 22 - 24 ], South Korea [ 28 ], Belgium [ 29 ], and Singapore [ 30 , 31 ]. The studies were published in 9 different journals and in symposium proceedings, most of which related to health informatics (9/16, 60%), followed by nursing sciences (3/16, 20%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations